Inuit Methods of Identifying Polar Bear Characteristics: Potential for Inuit Inclusion in Polar Bear Surveys + Supplementary Appendix Tables S1 to S5 (See Article Tools) - Wong, Pamela B.Y.; Murphy, Robert W. (ARCTIC, 2016)
As a result of their close proximity to and frequent interactions with polar bears, Inuit hunters are aware of changes in polar bear population ecology and characteristics. This valuable information could contribute to any polar bear research or monitoring program. Understanding how Inuit gather ecological information on polar bears and how this knowledge is shaped by individual experiences can also overcome any barriers to Inuit inclusion in bear monitoring and management. On the basis of interviews in four Nunavut communities, we report Inuit hunting experiences and methods of identifying polar bear sex, age, body size, and health status. Across communities, Inuit share techniques in identifying and distinguishing bear characteristics that overlap with scientific methods, suggesting that Inuit could provide immediate and inexpensive information to polar bear research programs. Hunting preferences are shaped by individual experiences with polar bears (e.g., through hunting or bear encounters), as well as familiarity with polar bear research and management. Identifying and incorporating community perspectives in management will be necessary to sustain local support for programs that affect Inuit knowledge formation and persistence. En raison de leur grande proximité des ours polaires et de leurs interactions fréquentes avec ceux-ci, les chasseurs inuits prennent connaissance de changements qui s’opèrent sur le plan de l’écologie et des caractéristiques de la population d’ours polaires. Cette précieuse information pourrait jouer un rôle dans n’importe quel programme de recherche ou de surveillance d’ours polaires. Le fait de comprendre comment les Inuits recueillent des renseignements de nature écologique sur les ours polaires et comment ces connaissances sont moulées par les expériences de chacun pourrait permettre de surmonter les obstacles en matière d’inclusion des Inuits aux travaux de surveillance et de gestion des ours. À la lumière d’entretiens réalisés dans quatre collectivités du Nunavut, nous faisons ...